2014
DOI: 10.2478/intag-2013-0031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil tillage and erosion on the dispersion of glyphosate and aminomethylphosphonic acid in agricultural soils

Abstract: A b s t r a c t. Erosion processes can strongly influence the dissipation of glyphosate and aminomethylphosphonic acid applied with Roundup Max® in agricultural soils; in addition, the soil structure state shortly before erosive precipitations fall can be a key parameter for the distribution of glyphosate and its metabolite. Field rain simulation experiments showed that severe erosion processes immediately after application of Roundup Max® can lead to serious unexpected glyphosate loss even in soils with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
(33 reference statements)
2
39
0
Order By: Relevance
“…Many studies have focused on glyphosate adsorption, degradation, and leaching in environments, but little is known about glyphosate transport associated with soil erosion (Borggaard and Gimsing, 2008;Donald, 2002). Laitinen et al (2009) andTodorovic et al (2014) had experimented (plot observations) under field conditions but only reported glyphosate transport by runoff. Thus, the proposal of the present study was to quantify the transport of glyphosate and AMPA associated with runoff and erosion in Chinese loess soils.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Many studies have focused on glyphosate adsorption, degradation, and leaching in environments, but little is known about glyphosate transport associated with soil erosion (Borggaard and Gimsing, 2008;Donald, 2002). Laitinen et al (2009) andTodorovic et al (2014) had experimented (plot observations) under field conditions but only reported glyphosate transport by runoff. Thus, the proposal of the present study was to quantify the transport of glyphosate and AMPA associated with runoff and erosion in Chinese loess soils.…”
Section: Introductionmentioning
confidence: 97%
“…The free forms of glyphosate and AMPA are thus easily dispersed, especially in wet soils due to preferential flow (Vereecken, 2005), and heavy rains shortly after glyphosate application increase the entry of glyphosate to surface water bodies through transport with runoff and suspended load (Botta et al, 2009;Candela et al, 2010;Gjettermann et al, 2009;Peruzzo et al, 2008;Stone and Wilson, 2006;Vereecken, 2005). Luijendijk et al (2003) reported that up to 24% of the glyphosate sprayed on hard surface soil was transported in runoff to surrounding fields, and Todorovic et al (2014) showed that approximately 47% of applied glyphosate was transported in the runoff associated with erosion and tillage managements (plough or not). The solubility of glyphosate contributes much to its contamination of surface water, but glyphosate and AMPA bound to particles suspended in water is another means of glyphosate and AMPA transport, known as particle-facilitated transport (Rügner et al, 2014;VandeVoort et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Particulate transport via water erosion is an important pathway for glyphosate and AMPA towards surface water bodies (Todorovic et al, 2014;Yang et al, 2015). In fact, after a 60 min rain simulation at a rain intensity of 1 mm min Yang et al (2015) observed that 4-5% of the initially applied glyphosate was lost/transported by runoff in the dissolved phase while 8-11% of the applied glyphosate was transported by the suspended load.…”
Section: Off-site Transport By Wind and Water Erosionmentioning
confidence: 99%